Daughters of the moon, sisters of the sun : young women & mentors on the transition to womanhood - Hughes, K. Wind (Karen Wind), 1954-; Wolf, Linda, 1950- (desLibris. Books collection., 1997)
Twenty-one young women share life lessons, coming-of-age stories, and interviews with the remarkable women who influenced their growth.